Interaction induced shifts in O-H stretching frequency of water in halide-ion water clusters: a microscopic approach with a bond descriptor - Tanwar, Akhilesh; Bagchi, Biman; Pal, Sourav (Journal of Chemical Physics, 2006)
Based on conceptual density functional theory, two new descriptors, the normalized atom-condensed Fukui functions (NFFs) and bond deformation kernel (BDK), are proposed to describe the O-H stretching frequency shifts in water halide-ion clusters by including local polarizations in the system. NFF, along with BDK, can be successfully used to describe interactions between different atoms, especially in cases where polarizations are quite important. (c) 2006 American Institute of Physics.

Influence of electric field on the global and local reactivity descriptors: reactivity and stability of weakly bonded complexes - Kar, Rahul; Chandrakumar, K. R. S.; Pal, Sourav (Journal of Physical Chemistry A, 2007)
The response of the global and local reactivity density-based descriptors (chemical potential, hardness, softness, Fukui function, and local softness) in the presence of external electric field has been studied for some of the simple prototype molecular systems. In addition to the analysis on the reactivity of these systems, the influence of the electric field on the interaction energy of the complexes formed by these systems has also been studied using the recently proposed semiquantitative model based on the local hard-soft acid-base principle. By using the inverse relationship between the global hardness and softness parameters, a simple relationship is obtained for the variation of hardness in terms of the Fukui function under the external electric field. It is shown that the increase in the hardness values for a particular system in the presence of external field does not necessarily imply that the reactivity of the system would be deactivated or vice versa.

Intermediate hamiltonian hilbert space coupled cluster method: theory and pilot application - Eliav, Ephraim; Borschevsky, Anastasia; Shamasundar, K. R.; Pal, Sourav; Kaldor, Uzi (International Journal of Quantum Chemistry, 2009)
The intermediate Hamiltonian state universal (Hilbert-space) coupled-cluster method is presented, using a formalism similar to that developed for the valence universal (Fock-space) approach. The method is expected to be applicable to many states not accessible by traditional multiroot multireference all-order size-extensive approaches. A pilot application to excited states of atomic beryllium shows good convergence and agreement with experiment and full CI values. (C) 2009 Wiley Periodicals, Inc. Int J Quantum Chem 109: 2909-2915, 2009
Keywords: coupled cluster; Hilbert space; intermediate Hamiltonian

Ionization potential and structure relaxation of adenine, thymine, guanine and cytosine bases and their base pairs: a quantification of reactive sites - Mishra, Deepti; Pal, Sourav (Journal of Molecular Structure-Theochem, 2009)
We present density functional theory (DFT) calculations using B3LYP/6-31++G** method to show relaxation in geometry of base pairs on cation radical formation. The changes in hydrogen bond length and angles show that in the cationic radical form the structure of the base pairs relaxes due to the distribution of charge. According to a recent study. it has been found that, upon excitation hole transfer from base to sugar occurs which results in sugar radical formation and leads to strand breakage 145] [A. Kumar, M.D. Sevilla, J. Phys. Chem. B 110 (2006) 24181]. One hydrogen bond increases, while the other decreases in Adenine-Thymine (AT) base pair and in case of Guanine-Cytosine (GC) base pair. one bond increases and other two decrease. Same is the case with bond angles for both the base pairs. Analysis of the electron density map of Singly Occupied Molecular Orbital (SOMO) reveals that electron is transferred mainly from adenine and guanine bases in the cationic radical formation of AT and CC base pair, respectively. The reactive sites of bases have been analyzed using condensed Fukui functions in a relaxed and frozen core approximation. The effects of relaxation on the reactivity indices are also analyzed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Base-pairs; DNA bases; Fukui function; H-bond length; Ionization potential

Influence of plane wave cut-off on structural and electronic properties in Sn-BEA and Ti-BEA zeolite water molecule interaction - Kulkarni, Bhakti S.; Krishnamurty, Sailaja; Pal, Sourav (Chemical Physics Letters, 2010)
Periodic systems are best described by the pseudo-potential methods. However, the accuracy of its description depends on the cut-off of plane wave basis. This is much more critical in the case of weak interactions, where a clear understanding on the influence of plane wave cut-off on the structural and electronic properties is not readily available in the literature. In the present work, we have taken a metal substituted beta zeolite-H2O complex for understanding this objective. Our studies show that while a lower cut-off of 500 eV is sufficient for the convergence of the structural parameters, description of energy-dependent properties necessitates a high cut-off value. (C) 2009 Elsevier B.V. All rights reserved.

Influence of charge and ligand on the finite temperature behavior of gold clusters: a BOMD study on Au-6 cluster - Manzoor, Dar; Pal, Sourav; Krishnamurty, Sailaja (Journal of Physical Chemistry C, 2013)
Conformation and electronic charge on a gold cluster are known to determine its catalytic property. However, little is known on the finite temperature behavior of various gold cluster conformations. Much less is known on the role of charge or a ligand in stabilizing a conformation at finite temperatures. In this work, we have carried out relativistic density functional theory (DFT) based molecular dynamical simulations on neutral and charged Au-6 clusters with an aim of understanding the stability of ground state conformations as a function of charge on the cluster. Our simulations reveal that cationic and anionic Au-6 clusters undergo conformational transitions at 500 K where as neutral Au-6 cluster retains its ground state conformation up to a temperature of 1100 K. In order to look into the factors leading to the stabilization of neutral Au-6 cluster (or destabilization of cationic and anionic Au-6 clusters), structural and electronic properties are analyzed. Factors such as charge redistribution within the atoms and composition of molecular orbitals are seen to contribute towards stronger Au-Au bonds in Au-6(0) thereby stabilizing it considerably. Following the analysis, simulations are also extended to neutral, cationic, and anionic Au-6-COn (n = 1,2) complexes. In the case of CO chemisorbed Au-6 clusters, neutral and negatively charged ground state conformations are stable up to nearly 800 K, while the positively charged Au-6 ground state conformation collapses at room temperature. This work, in short demonstrates how charge or even a ligand can be used to moderate the physical properties of a gold cluster.

Interatomic coulombic decay in (HF)n,(n=2-3) clusters using CAP/EOM-CCSD method - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Molecular Physics, 2013)
The equation-of-motion coupled-cluster method along with the complex absorbing potential has been applied to study the interatomic Coulombic decay mechanism in hydrogen-bonded clusters. We have applied this method to calculate the lifetime of the F 2s inner-valence ionised state of (HF)(n) (n = 2-3) clusters. The lifetime is found to be very short and decreases substantially with increasing the number of HF monomer.
Keywords: complex absorbing potential (CAP); equation-of-motion coupled-cluster (EOM-CC); HF clusters; interatomic Coulombic decay (ICD)

Intermediate hamiltonian fock space multireference coupled cluster approach to core excitation spectra - Dutta, Achintya Kumar; Gupta, Jitendra; Vaval, Nayana; Pal, Sourav (Journal of Chemical Theory and Computation, 2014)
The Fock space multireference coupled cluster (FSMRCC) method provides an efficient approach for the direct calculation of excitation energies. In intermediate Hamiltonian (IH-FSMRCC) formulation, the method is free from intruder state problems and associated convergence difficulties, even with a large model space. In this paper, we demonstrate that the IH-FSMRCC method with suitably chosen model space can be used for the accurate description of core excitation spectra of molecules, and our results are in excellent agreement with the experimental values. We have investigated the effect of choice of model space on the computed results. Unlike the equation-of-motion (EOM)-based method, the IH-FSMRCC does not require any special technique for convergence and in singles and doubles approximation gives a performance comparable to that of the standard EOMEE-CCSD method, even better in some of the cases.

Implementation of the Z-vector method in the relativistic-coupled-cluster framework to calculate first-order energy derivatives: Application to the SrF molecule - Sasmal, Sudip; Pathak, Himadri; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2015)
The molecular dipole moment and magnetic hyperfine-structure constant demand an accurate wave function far from the nucleus and in the near nuclear region, respectively. We, therefore, employ the so-called Z-vector method in the domain of relativistic-coupled-cluster theory to calculate the first-order property of molecular systems in their open-shell ground-state configuration. The implemented method is applied to calculate the molecular dipole moment and parallel component of the magnetic hyperfine-structure constant of the SrF molecule. The results of our calculation are compared with the experimental and other available theoretically calculated values. We are successful in achieving good accordance with the experimental results. The result of our calculation of the molecular dipole moment is in the accuracy of similar to 0.5%, which is clearly an improvement over the previous calculation based on the expectation value method in the four-component coupled-cluster framework [V. S. Prasannaa et al., Phys. Rev. A 90, 052507 (2014)]. Thus, it can be inferred that the Z-vector method can provide an accurate wave function in both the near and far nuclear region, which is evident from our calculated results.

Influence of carbon and phosphorus doping on electronic properties of ZnO - Sharma, Vidhika; Prasad, Mohit; Jadkar, Sandesh; Pal, Sourav (Journal of Materials Science-Materials in Electronics, 2016)
ZnO is one of the most promising candidate for photoelectrochemical splitting of water for hydrogen production. To increase the efficiency of ZnO based photoelectrochemical cell, its band-gap and band edges should be tailored to match visible light spectra and water redox potential respectively. In this paper, First-principles density functional theory calculations have been performed to evaluate the effect of non-metal dopants on electronic properties of ZnO. The model structures of X-doped ZnO were constructed using 32-atom 2 x 2 x 2 supercell of wurtzite ZnO with one O atom replaced with X (carbon C, phosphorus P). With respect to the electronic band structure, C (2p), P (3p) states are located above the valence band maximum of ZnO and mixing of these states is feeble to produce significant band gap narrowing. Doping of these non-metals dopants helps in the creation of isolated states which enhances visible light absorption of ZnO. Our theoretical calculations are consistent with the experimental results of C (P) doped ZnO and fully explains its visible light activity on non-metal doping.

Interatomic Coulombic decay in Neon-Helium cluster: a complex absorbing potential based equation-of-motion coupled cluster investigation - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Molecular Physics, 2021)
The interatomic Coulombic decay (ICD) of the Ne(2s(-1)) and Ne(2s(-1)2p(-1)) states in neon-helium dimer is studied using highly accurate complex absorbing potential based equation-of-motion coupled cluster (CAP-EOMCC) method. The ICD decay process for the Ne(2s(-1)) state in neon-helium dimer is closed at its equilibrium bond distance. However, the decay channel is open at large bond distance of 6.2 angstrom. The decay channel for the double ionised Ne(2s(-1)2p(-1)) state is open at 3.46 angstrom. From our calculations, we have noticed that the decay rate of Ne(2s(-1)2p(-1)) state in neon-helium dimer is four times faster compared to the Ne(2s(-1)) state. We have also investigated how the decay rate of Ne(2s(-1)) state in neon-helium cluster varies in the presence of different helium environment. [GRAPHICS] .
Keywords: double ionised state; equation-of-motion coupled cluster (EOMCC); He droplet; interatomic Coulombic decay (ICD)